Perbedaan Kadar Hemoglobin Segera Diperiksa dan Penundaan 2,5 Jam Pada Suhu Ruang - Indah Sari; Ema Karlina; Bastian (jurnal kesehatan terapan sains dan teknologi, 2023)
Hemoglobin is a protein molecule in red blood cells that functions as a means of transporting oxygen (O2) from the lungs to tissues throughout the body and taking carbon dioxide (CO2) from the tissue below to the lungs to be released into the free air. This study aims to determine the effect between blood immediately examined and a delay of 2.5 hours at room temperature on hemoglobin levels conducted at IKesT Muhammadiyah Palembang. The type of research used is cross sectional with intact group comparison research design. The sample consisted of 30 samples immediately examined and 30 samples with a delay of 2.5 hours taken from 30 respondents. The study was conducted starting from patient preparation, taking examination materials, processing examination materials, analysis and research results. The average hemoglobin level immediately examined was 12.8 g/dL while the hemoglobin level with a delay of 2.5 hours was 12.7 g / dL, the results of the wilxocon test showed that the significant value was p=0.342. The p value obtained is p>0.05. The results can be concluded that there is no difference in hemoglobin levels immediately examined and a delay of 2.5 hours at room temperature.